Shear wave splitting catalogue, Rutford Ice Stream (West Antarctica), November 2018 to February 2019 ... - Kufner, Sofia-Katerina; Brisbourne, Alex; Smith, Andrew; Wookey, James; Martin, Carlos; Hudson, Thomas; Kendall, John Michael (NERC EDS UK Polar Data Centre, 2022)
This dataset contains an ASCII file with shear wave splitting results for 202,652 station-event pairs from glacial micro-seismicity, recorded from a 35-station seismic network located ~40 km upstream of the grounding line of Rutford Ice Stream, West Antarctica. Microseismicity is located at the base of the ice stream at ~2.2 km depth (relative to the ice surface). Seismic waveform data, which was used to calculate shear wave splitting parameters is provided in miniseed format. Event hypocenter information, event times and coordinates of receiving stations are listed in the ASCII file. Shear wave splitting was calculated using the software MFAST. Shear wave splitting parameters can be used to determine seismic anisotropy along the ray path, which helps to characterise ice fabric. This work was funded within the BEAMISH project by NERC AFI award numbers NE/G014159/1 and NE/G013187/1. Seismic instruments were provided by NERC SEIS-UK (Loan 1017) and the Incorporated Research Institutions for Seismology (IRIS) ... : Icequake used for shear wave splitting analysis are chosen based on the event catalogue of Kufner et al. (2021). To calculate SWS parameters from the waveform data of these events, horizontal seismograms are filtered between 8 and 125 Hz, using a two-pole Butterworth filter, and downsampled from 1000 to 500 Hz. The MFAST (M. K. Savage et al., 2010) software is used for shear wave splitting analysis. MFAST implements a minimum eigenvalue analysis algorithm (Silver & Chan, 1991) to calculate shear wave splitting in multiple time windows around the S-onset. A cluster analysis method is then implemented on the splitting results from individual measurement windows to find the most stable set of splitting parameters (see Teanby et al. (2004) for more details). In MFAST, the start and end point of the measurement windows are variable, dependent on an event's dominant frequency. Detailed information on the methodology and interpretation of the results will be presented in Kufner et al. (in prep.). ...